An Analysis of Interference and Integration in 3rd Semester Students of French Literature Department at Halu Oleo University - Liber, Dewi Srikandi; Nuru, Sarniati (Asian Journal of Multidisciplinary Research, 2025)
This study investigates the student’s utterances during the learning process. This study focuses on some aspects of interference and integration such as: Interference phonolgy, Interference Syntaksis, Interference Morphology and Integration. This research employs descriptive qualitative. The sources of data in this research were taken from 3rd Semester students of French Literature at Halu Oleo University while the data in this research are in the form of utterances. The data is analysed using Jendra (1991:108) theory of Interference and Weinrich (1970:64-65) theory of factors that cause interference. The result showed that from the 8 data, only 2 were exist type of interference, namely Interference phonology and Interference Syntaxis, and 4 data for Integration. Where the factor causes the interference are bilingualism and Carrying out Mother Language Habits.